THEORETICAL FOUNDATIONS OF THE TECHNOLOGICAL PARAMETERS OF A STRAIGHT-FLOW FIBER SEPARATION DEVICE - Majidov, Abduvali (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article discusses theoretical studies including the investigation of the fiber separation process from the seed during ginning depending on the density of the seed and fiber and the change in the inclination angle of the ginning rollers over a unit of time, the development of a mathematical model of the straight-flow fiber separation process, and the statistical analysis of the technological process in a straight-flow fiber separation device.